Ice shelf fracture parameterization in an ice sheet model - Sun, Sainan; Cornford, Stephen L.; Moore, John C.; Gladstone, Rupert; Zhao, Liyun (The Cryosphere, 2017)
Floating ice shelves exert a stabilizing force onto the inland ice sheet. However, this buttressing effect is diminished by the fracture process, which on large scales effectively softens the ice, accelerating its flow, increasing calving, and potentially leading to ice shelf breakup. We add a continuum damage model (CDM) to the BISICLES ice sheet model, which is intended to model the localized opening of crevasses under stress, the transport of those crevasses through the ice sheet, and the coupling between crevasse depth and the ice flow field and to carry out idealized numerical experiments examining the broad impact on large-scale ice sheet and shelf dynamics. In each case we see a complex pattern of damage evolve over time, with an eventual loss of buttressing approximately equivalent to halving the thickness of the ice shelf. We find that it is possible to achieve a similar ice flow pattern using a simple rule of thumb: introducing an enhancement factor ∼ 10 everywhere in the model domain. However, spatially varying damage (or equivalently, enhancement factor) fields set at the start of prognostic calculations to match velocity observations, as is widely done in ice sheet simulations, ought to evolve in time, or grounding line retreat can be slowed by an order of magnitude.